Apocalypse, Gothic and Rupturing of Societal Hierarchy: An Interpretation of Marxian Tendencies in Pride and Prejudice and Zombies - Sanghamitra Ghatak (IAFOR Journal of Arts & Humanities)
The assertion by Karl Marx that “there must be something rotten in the very core of a social system which increases its wealth without diminishing its misery” serves as a profound critique of socio-economic structures, resonating in contemporary socio-political contexts. This statement captures the enduring tensions inherent in capitalist systems, where the accumulation of wealth often coexists with the perpetuation of human suffering. The modern adaptation of Jane Austen’s Pride and Prejudice, particularly the 2009 film Pride and Prejudice and Zombies, illustrates this dynamic by integrating a gothic and apocalyptic dimension into the narrative. The depiction of a zombie apocalypse in this context can be interpreted as an embodiment of Marx’s critique, where the capitalist system thrives at the expense of the working class, metaphorically represented by the blood-sucking zombies. These creatures, driven by an insatiable hunger for human flesh, mirror the capitalist exploitation of labor, where workers are drained of their vitality in a system that survives and flourishes on their suffering.